2020
DOI: 10.4103/jehp.jehp_13_20
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of supporting nursing students in clinical education

Abstract: Clinical education requires creating a supportive atmosphere for learners and nursing students, who need support to be prepared for their future profession. The purpose of this study is to investigate the challenges of supporting the nursing students in clinical education. This article reviewed studies conducted between 2009 and 2019 with the keywords including support, challenge, students, education, and nursing using SID, Magiran, IranMedex, Google Scholar, Elsevier, and PubMed as databases. Among the 926 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
1
14
0
1
Order By: Relevance
“…It found that nursing students faced several challenges in connection with clinical practice such as anxiety and fear, ineffective clinical education, organizational-environmental stress, and socio-cultural challenges. However, most studies only highlighted the presence of such challenges, while few studies dealt with their causes [ 29 ]. This pilot-study aimed to evaluate a new concept of clinical practice to create a new clinical learning environment to support nursing students’ independence and well-being, increase the feeling of belonging, strengthen the relationship with the healthcare staff, and facilitate the transition from student to working life.…”
Section: Discussionmentioning
confidence: 99%
“…It found that nursing students faced several challenges in connection with clinical practice such as anxiety and fear, ineffective clinical education, organizational-environmental stress, and socio-cultural challenges. However, most studies only highlighted the presence of such challenges, while few studies dealt with their causes [ 29 ]. This pilot-study aimed to evaluate a new concept of clinical practice to create a new clinical learning environment to support nursing students’ independence and well-being, increase the feeling of belonging, strengthen the relationship with the healthcare staff, and facilitate the transition from student to working life.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers concluded that nursing faculty caring behaviors are instrumental in motivating student progression through the curriculum and faculty support plays a significant role in students’ academic success in relation to both classroom and clinical learning 16,17. Jafarian-Amiri et al17 added that clinical education requires a caring environment that fosters a supportive atmosphere and clinical stressors must be mitigated by nursing faculty. Faculty support and creating a safe space for learning in the online classroom environment was also essential to classroom learning 18…”
Section: Relevant Literaturementioning
confidence: 99%
“…Several systematic reviews were conducted that examined the impact of perceived faculty support and caring on nursing students. The researchers concluded that nursing faculty caring behaviors are instrumental in motivating student progression through the curriculum and faculty support plays a significant role in students’ academic success in relation to both classroom and clinical learning 16,17. Jafarian-Amiri et al17 added that clinical education requires a caring environment that fosters a supportive atmosphere and clinical stressors must be mitigated by nursing faculty.…”
Section: Relevant Literaturementioning
confidence: 99%
“…This interaction with the real-life workplace provides nursing students with the opportunity to apply their theoretical knowledge to clinical practice, develop their professional identity and contemplate their future careers [ 1 , 2 ]. However, despite its multifaceted benefits, learning within the clinical environment is not without its obstacles, with students challenged by lack of access to adequate supervision, suboptimal learning encounters and passive involvement in clinical tasks [ 3 , 4 ]. Such experiences of clinical placement are problematic, given the demonstrated association between student satisfaction with clinical placement and learning outcomes, motivation to continue their nursing education and student well-being [ 2 ].…”
Section: Introductionmentioning
confidence: 99%